Towards Pluricentricity: On the Names of Parcel Terminals in the Russian Speaking Space - Sinočkina, Birutė (Literatūra, 2025)
The emergence of innovations in life entails changes in speech, particularly vocabulary. This article aims to analyze neologisms of the Russian language generated by technological innovations. Automated parcel terminals have become an integral part of everyday life, allowing users to receive and send parcels at a convenient place and time, regardless of the opening hours of postal institutions. However, despite their widespread use, there is no unity in the Russian-speaking community regarding the name of these self-service devices. Different countries use different Russian names, primarily focused on the names of these machines in the language of the titular nation, as well as emphasizing various aspects of their functioning, such as postal, parcel, and package. The inclusion of the word почтомат (transliterated as pochtomat) in the spelling dictionary of the Russian Academy of Sciences (2023), having codified the neologism in Russia, did not make this form of the word mandatory for the Russian language outside the Russian Federation, which indicates growing linguistic pluricentricity.
Keywords: pakomat; postamat; paštomatas; почтомат; paczkomat; pluricentricity